EFFECT OF VARIOUS TYPES OF GROWING MEDIA AND APPLICATION OF LIQUID ORGANIC FERTILIZER ON THE GROWTH OF DENDROBIUM ORCHIDS - I Dewa Made Arthagama; I Made Dana; Putu Perdana Kusuma Wiguna (International Journal of Biosciences and Biotechnology, 2021)
This research was a potted experiment carried out in a special orchid house (arnet) at the Padang Galleria Padangsambian Kelod from September to November 2019, the aim was to determine the effect of plant media and the provision of liquid organic fertilizers on the growth of dendrobium orchids. The factorial CRD pattern was the design used in this study, which consists of two factors, first, the use of growing media of wood charcoal (K), fern stems (P), and a mixture of fern stems with wood charcoal (M) and, second, the provision of liquid organic fertilizer, namely, Dewa (D), DI Grow (I), and GDM (G). The results showed that the interaction between the use of planting media and the application of liquid organic fertilizer had no significant effect on all plant growth parameters such as plant height, number of leaves, and number of tillers. However, the plant medium as a single treatment had a significant effect on the number of orchid tillers, fern stems (P) as the plant medium gave the highest number of tillers, namely: 2.22 stems or 32.93% more than the growing media for wood charcoal (K) and a mixture of charcoal, wood and fern stems (M) with 1.67 tillers each